Ausbildungskosten und -nutzen und die betriebliche Nachfrage nach Lehrlingen - Wolter, Stefan C. [Verfasser] (My University, 2008)
"Considerable improvements in the measurement of costs and benefits of apprenticeship training from the perspective of training companies have been made in the past few years. They have helped to better understand, why some firms train and others do not. With these micro-data sets we are also able to analyse measures that would help to increase the supply of training posts in an economy. A simulation of the impact of financial incentives on the training propensity of firms is made and shows that such a measure would be highly inefficient from an economic perspective. Further improvements in data are expected and should give valuable guidance in the design of educational, fiscal and labour market policies with respect to apprenticeship training." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; Betriebliche Berufsausbildung; Duales System; Kosten-Nutzen-Analyse; Schweiz